2020
DOI: 10.1093/cid/ciaa641
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of C-Reactive Protein in Patients With Coronavirus 2019

Abstract: Background Elevated serum C-reactive protein (CRP) level was observed in most patients with COVID-19. Methods Data of COVID-19 patients with clinical outcome in a designated hospital in Wuhan, China, were retrospectively collected and analyzed from Jan 30 to Feb 20, 2020. The prognostic value of admission CRP was evaluated in patients with COVID-19. Results O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
238
3
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(332 citation statements)
references
References 20 publications
36
238
3
18
Order By: Relevance
“…However, some differences also exist. Increasing age was strongly associated with poorer outcomes, corroborating the findings of others [3,[6][7][8]17,18]. In line with previous research [19,20] a strong association between respiratory diseases and death was found.…”
Section: Discussionsupporting
confidence: 91%
“…However, some differences also exist. Increasing age was strongly associated with poorer outcomes, corroborating the findings of others [3,[6][7][8]17,18]. In line with previous research [19,20] a strong association between respiratory diseases and death was found.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, studies have reported that patients infected with COVID-19 show increased levels of pro-inflammatory neutrophils, procalcitonin, CRP and IL-6 (Chen et al, 2020;Zeng et al, 2020). Moreover, studies have reported that the neutrophil count, IL-6 and CRP can be used as predictors of clinical outcome and disease severity Luo et al, 2020;Qin et al, 2020). Recently, some studies have shown that cancer patients with COVID-19 have higher level of CRP, and higher neutrophil counts, D-dimer and LDH are associated with poor prognosis (Mehta et al, 2020;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have reported that pro-inflammatory factors such as CRP, interleukin 6, neutrophils, etc. were associated with the severity and prognosis of patients with COVID-19 Luo et al, 2020;Moore and June, 2020;Sahu et al, 2020). In patients with COVID-19, high levels of pro-inflammatory factors predicted a poor prognosis (Zeng et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…Twenty-two studies [20,26,74,[82][83][84][85][86][87][88][89][90][91][92][94][95][96][97][98][99][100]102] showed higher D-Dimer levels in 1149 subjects dead with COVID-19 as compared to 4407 subjects survived to COVID-19 (SMD: 3.88; 95%CI: 2.70, 5.07, p < 0.001, Figure 3). The heterogeneity among studies was significant (I 2 : 99.4%, p < 0.001) and was not reduced by the exclusion of one study at a time.…”
Section: Study Group 2 (Dead With Covid-19 Vs Survived To Covid-19)mentioning
confidence: 98%